Seniors in cities and senior-friendly cities analysis for selected Polish cities – robust taxonomic approach - Trzpiot, Grażyna (Seniorzy w miastach i analiza miast przyjaznych seniorom dla wybranych miast polskich – odporne podejście taksonomiczne, 2020)
The purpose of the article is to assess selected large cities in Poland as senior-friendly. Using the municipal population forecast for 2017-2030 published in 2017, together with the available database, own analyses were made for selected cities in Poland. Additionally for the description of ‘senior-friendly’ cities, it was assumed that the starting point is the WHO definition, which indicated four main criteria determining whether a given city can be considered to be friendly to the elderly. In a city friendly to seniors, the principles, services, environment and structures built up support the active ageing process and avail it for the residents. For the purposes of the research, taking into account the above objectives and based on published sources, a descriptive model was created. The study assessed selected Polish cities as senior-friendly cities, using the robust taxonomic approach
Econometrics = Ekonometria, 2020, Vol. 24, No. 2, s. 30-40
Keywords: elderly people; senior safety; robust taxonomic analysis; osoby starsze; bezpieczeństwo seniorów; odporna analiza taksonomiczna